In vitro simulation of the bioavailability of fluoride in food roasted with high-fluoride fuel and its health risks - Zhang, Jianghui; Luo, Guomei; Tu, Chenglong; Yang, Na; Tang, Kuo; Tu, Chenghua (Frontiers in Nutrition, 2025)
Fluorosis in coal-burning areas of Southwest China is exacerbated by multi-pathway fluoride exposure, with diet emerging as a critical factor due to traditional food preparation methods. This study systematically evaluated fluoride accumulation, bioavailability, and health risks associated with foods roasted over high-fluoride coal, with a particular focus on chili—a dietary staple with heightened fluoride absorption and bioavailability. Results indicated that after 30 days of roasting, chili's fluoride content reached 869.82 mg·kg−1, with bioavailability levels between 2.18 and 12.00%, making it the largest contributor to the hazard index (HI), accounting for over 80% of the total when bioavailability was considered. In comparison, corn, tofu, and pork, though accumulating fluoride to varying extents, presented lower bioavailability, and thus relatively lower health risks. Recent dietary shifts in the region show reduced corn consumption and increased chili and pork intake, further shifting dietary fluoride exposure risk toward high-bioavailability foods like chili. These findings highlight the need for dietary management interventions in high-fluoride regions, prioritizing moderated chili consumption and revised cooking practices to mitigate fluorosis risk effectively.